POLA KEBERAGAMAAN MASYARAKAT MARGINAL - Ahmad Muttaqin (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2014)
This is a research on sociology of religion, focusing on the issue of religious practices in a local community. Kampung Laut was chosen as the setting of this research for two reasons. First, the rituals of religion practices in the region are different from mainstream practices, which result in label and justification that their religiosity is not a part of or only a fragment of the mainstream religion and tend to be the target of correction. Second, this region raises conflicts among government institutions in relation to the rights of natural resources possession and utilization. The bad image built through this marginalization has formed Kampung Laut community as the one that is resistant and latent. This research used descriptive qualitative method with sociological approach. Rituals of religious practices that are different from the mainstream are explained on the basis of Weber’s theory of behavior categorized into value-oriented rationality. This kind of practices is considered to be more beneficial in the context of struggling for identity among the practices of marginalization experienced by Kampung Laut community. This condition gives a description to public that Kampung Laut community receives unfair treatments for their natural resources. Religious issues is made an entry for its massive, communal, and related to transcendental values.